Flow cytometric analysis of cerebrospinal fluid in adult patients with acute lymphoblastic leukemia during follow‐up. (15th January 2018) - Gong, Xiaoyuan; Lin, Dong; Wang, Huijun; Wang, Ying; Liu, Bingcheng; Wei, Hui; Zhou, Chunlin; Liu, Kaiqi; Wei, Shuning; Gong, Benfa; Zhang, Guangji; Liu, Yuntao; et al.
Abstract: Objective: To explore the value of flow cytometric (FCM) analysis of cerebrospinal fluid (CSF) in the diagnosis of central nervous system involvement in adult patients with acute lymphoblastic leukemia (ALL) during follow‐up. Methods: A total of 2871 CSF samples from 357 adult patients with newly diagnosed ALL between the year of 2009 and 2015 were analyzed retrospectively. These patients were divided into 3 groups according to CSF results, FCM+/conventional cytology (CC)+ group, FCM+/CC− group, and FCM−/CC− group, respectively. The overall survival (OS) of the three groups was analyzed. Results: Fifteen (4.2%) and 26 (7.3%) patients' CSF samples were FCM+/CC+ and FCM+/CC−, respectively. The remaining 316 (88.5%) patients' samples were FCM−/CC−. The 2‐year OS for the FCM+/CC+, FCM+/CC−, and FCM−/CC− groups was 40.0%, 20.6%, and 64.2%, respectively ( P  <   .001). There was no statistically significant difference in OS between FCM+/CC+ and FCM+/CC− patients ( P  =   .195). In multivariate analysis, a high WBC count and LDH level were independent risk factors for central nervous system involvement in adult patients with ALL. Conclusions: FCM demonstrated a superior sensitivity over conventional cytology in the diagnosis of central nervous system involvement in adult patients with ALL. FCM+/CC− patients showed a similar survival with FCM+/CC+ patients, suggesting that an isolated FCM‐positive status holds clinical significance.